If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9 + w)(5w + -6) = 0 Reorder the terms: (9 + w)(-6 + 5w) = 0 Multiply (9 + w) * (-6 + 5w) (9(-6 + 5w) + w(-6 + 5w)) = 0 ((-6 * 9 + 5w * 9) + w(-6 + 5w)) = 0 ((-54 + 45w) + w(-6 + 5w)) = 0 (-54 + 45w + (-6 * w + 5w * w)) = 0 (-54 + 45w + (-6w + 5w2)) = 0 Combine like terms: 45w + -6w = 39w (-54 + 39w + 5w2) = 0 Solving -54 + 39w + 5w2 = 0 Solving for variable 'w'. Factor a trinomial. (-9 + -1w)(6 + -5w) = 0Subproblem 1
Set the factor '(-9 + -1w)' equal to zero and attempt to solve: Simplifying -9 + -1w = 0 Solving -9 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -1w = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -1w = 0 + 9 -1w = 0 + 9 Combine like terms: 0 + 9 = 9 -1w = 9 Divide each side by '-1'. w = -9 Simplifying w = -9Subproblem 2
Set the factor '(6 + -5w)' equal to zero and attempt to solve: Simplifying 6 + -5w = 0 Solving 6 + -5w = 0 Move all terms containing w to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -5w = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -5w = 0 + -6 -5w = 0 + -6 Combine like terms: 0 + -6 = -6 -5w = -6 Divide each side by '-5'. w = 1.2 Simplifying w = 1.2Solution
w = {-9, 1.2}
| 1/3x-7/10=3/2x | | 5x+5=15x-4-10 | | 5y^2+40y+50=0 | | 29=h+9 | | 1/2a-1/4a=9 | | 4-3*ln(x)=-5 | | 5y^2-40y+50=0 | | 4s-e=5-4a+e | | 3y+1=6x-13 | | 4(k+5)=.16(18k+18) | | 1/4a-9=1/2a | | f(x)=x^2+5x-36 | | [-10-(64)/256= | | 12n-1n+3n= | | 10x-13y=-31 | | 1/2a-9=1/4a | | 10x-13y=-32 | | 2(3+7x)=118 | | 10+7*4=38 | | 3n+7n-4= | | 5y-25=99+y | | -8+4u=-32 | | 432/2/4325/34435 | | 4x+51=6x+9 | | 2n+7-n+2= | | x+7x-5= | | 56=6h | | 6y-25=95+y | | 24=c-8 | | 4x+7=23+2x | | 40+3x+20+x=180 | | https://homebase.schoolnet.com/files/assess_files/cf1ae17e-8d5e-4dca-981c-c9ee7af1d787/_s_I373865_1.png |